Modelling the responses to climate change of a Mediterranean forest managed at different thinning intensities: Effects on growth and water fluxes - Gracia, C. A.; Sabate, S.; Tello, E. (IMPACTS OF GLOBAL CHANGE ON TREE PHYSIOLOGY AND FOREST ECOSYSTEMS, 1998)
This study explores the effect of various climatic change scenarios over a 50 year period on plots managed at a range of thinning intensities. In order to determine how management practises can modify the effect of climatic change on Mediterranean Forests we integrated field experiments and the results of the GOTILWA model so as to take into account both water fluxes and forest structure interactions. The results show that the positive effects of atmospheric CO2 fertilisation, causing an increase in WUE, counteract with the negative effects of both temperature increase and rainfall decrease. Thinning might attenuate the effects of adverse conditions by reducing both leaf respiratory costs and the foliage turnover rate.
The following values have no corresponding Zotero field: periodical: IMPACTS OF GLOBAL CHANGE ON TREE PHYSIOLOGY AND FOREST ECOSYSTEMS pub-location: PO BOX 17, 3300 AA DORDRECHT, NETHERLANDS
Keywords: climate change; mediterranean forest; Modelling